The Competence of TheFifth Semester Students of English Department FKIP UKI Toraja in Writing Paragraph - Dan Mangoki (UKI TORAJA, 2017)
The Competence of theFifth Semester Students of English Department FKIP UKIToraja in Writing Paragraph. The objective of this research was to find out thecompetence of the fifth semester students of English department FKIP UKI Torajain writing paragraph. The writer used quantitative descriptive method. Thepopulation of this research was the fifth semester students of English departmentFKIP UKI Toraja in writing paragraph which consists of 119 students. The writerused random sampling method, which means that not all of the population weretaken as respondents. The writer choose 20 students as respondents. The dataobtained from the written test were tabulated and analyzed by using the percentagetechnique. The mean score of the student’s competence in writing paragraph was78.6 falls in good category. While the average of content was 16, the average oforganization was 14.9, the average of grammar was 15.15, the average ofvocabulary was 16.5 and the average of mechanic was 17.25. It means that theaverage of mechanic is higher than all of the average of student’s competence incomponent. Based on the result above, the writer concludes that the competence ofthe fifth semester students of English department FKIP UKI Toraja is good.